A New Sound Velocity Meter - Williamson, R. L.; Hodges, G.; Eady, E. (The International Hydrographic Review, 2015)
The design of a new instrument for measuring the velocity of sound in sea water with improved accuracy is described. A particular feature of the instrument is that it may be towed through the water without causing appreciable errors.